Best Solid Waste Management Practices at Amritapuri: A Case Study - Anandakrishnan, Unnithan; Ravi, Akash; Thomas Ajith, Tharun; V. , Viswanath; Muramthookil Thomas, Gevargis; S.N. , Jyothi (International Journal of Psychosocial Rehabilitation, 2020)
Solid waste management, in today’s world, has turned out to be a matter of great concern. Rapid urbanization and population explosion have made efficient solid waste management a big challenge for mankind. In these prevailing conditions, Amrita Vishwa Vidyapeetham, Amritapuri campus, has designed waste management methods that reduce the burden on urban local bodies by processing most of the waste generated by it in the campus itself. The paper analyzes the various waste management practices, like waste sorting, processing, and disposal, followed in the study area. The paper also explores the scope for further improvements to enhance the overall efficiency of the existing solid waste management system by providing innovative suggestions.